Ethanol Extract of Pseudo-stem Lemongrass (Cymbopogon citrates) and Basil Leaves (Ocimum sanctum) Increase Bactrocera (Diptera: Tephritidae) Fruit Fly Catches - Angelina Putri Ayu Lestari; I Putu Artayasa; Prapti Sedijani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2020)
The tropical climate in Indonesia supports the presence of many types of plants that have the potential to produce abundant vegetables and fruit, however the presence of fruit flies is an obstacle to fruit and vegetable productivity. Lemongrass and basil have been studied to contain several compounds that have the potential to control fruit fly attacks. This study aims to determine the effect of the ethanol extract of lemongrass pseudo stem (Cymbopogon citrates) and basil (Ocimum sanctum) leaves on the catch of Bactrocera fruit flies and to determine the concentration of the extract that has the highest number of catches. The method used in sampling was factorial randomized block design (RBD). The ethanol extract of the pseudo-lemongrass, the extract of basil leaves or the mixture of both extract (1:1) that was given at concentrations of 15%, 30% and 45% was dropped onto a piece of cotton and for then be put within a trap before placing on the tree. The cathes obtained from each extract at each concentration were observed if they show a significant difference in the number of fruit fly. Data were tested using analysis of variance (F test) at ÃÂ± = 0.05, followed by the Honest Significant Difference test (HSD). The results showed that the catch obtained from ethanol extract of lemongrass pseudo stem or from basil leaf ectract as well as ÃÂ from their mixture had a significantly higher number of Bactrocera fruit flies than without using these extracts. The difference in extract concentration did not cause a difference in the ability to attract fruit flies. The conclusion of this study is that there is an effect of the ÃÂ pseudo stem ethanol extract of lemongrass or basil leaf ectract as well as their mixture on the catch of Bactrocera fruit flies and these extract are recommended as non-synthetic pesticidesalternatives.